The association of maternal obesity and obstetric anal sphincter injuries at time of vaginal deliveryAJOG Global Reports at a Glance - Amin Tavakoli, MD; Viraj R. Panchal, MD; Genevieve R. Mazza, MD; Rachel S. Mandelbaum, MD; Joseph G. Ouzounian, MD, MBA; Koji Matsuo, MD, PhD (Elsevier, 2023)
BACKGROUND: The risk of third- and fourth-degree perineal laceration after vaginal delivery in patients with obesity is relatively understudied and has mixed findings in existing literature. OBJECTIVE: This study aimed to examine the association of maternal obesity and obstetric anal sphincter injuries at vaginal delivery. STUDY DESIGN: The Healthcare Cost and Utilization Project's National Inpatient Sample was retrospectively queried to examine 7,385,341 vaginal deliveries from January 2017 to December 2019. The exposure assignment was obesity status. The main outcomes were third- and fourth-degree perineal lacerations after vaginal delivery. Statistical analysis examining the exposure-outcome association included (1) inverse probability of treatment weighting with log-Poisson regression generalized linear model to account for prepregnant and pregnant confounders for the exposure and (2) multinomial regression model to account for delivery factors in the inverse probability of treatment weighting cohort. The secondary outcomes included (1) the temporal trends of fourth-degree laceration and its associated factors at cohort level and (2) risk factor patterns for fourth-degree laceration by constructing a classification tree model. RESULTS: In the inverse probability of treatment weighting cohort, patients with obesity were less likely to have fourth-degree lacerations and third-degree lacerations than patients without obesity (fourth-degree laceration: 2.3 vs 3.9 per 1000 vaginal deliveries, respectively; adjusted odds ratio, 0.62; 95% confidence interval, 0.56-0.69; third-degree laceration: 15.6 vs 20.1 per 1000 vaginal deliveries, respectively; adjusted odds ratio, 0.79; 95% confidence interval, 0.76-0.82). In contrast, in patients with obesity vs those without obesity, forceps delivery (54.7 vs 3.3 per 1000 vaginal deliveries, respectively; adjusted odds ratio, 17.73; 95% confidence interval, 16.17-19.44), vacuum-assisted delivery (19.8 vs 2.9 per 1000 vaginal deliveries, respectively; adjusted odds ratio, 5.18; 95% confidence interval, 4.85-5.53), episiotomy (19.2 vs 2.8 per 1000 vaginal deliveries, respectively; adjusted odds ratio, 3.95; 95% confidence interval, 3.71-4.20), and shoulder dystocia (17.8 vs 3.4 per 1000 vaginal deliveries, respectively; adjusted odds ratio, 2.60; 95% confidence interval, 2.29-2.94) were associated with more than a 2-fold increased risk of fourth-degree perineal laceration. Among the group with obesity, patients who had forceps delivery and shoulder dystocia had the highest incidence of fourth-degree laceration (105.3 per 1000 vaginal deliveries). Among the group without obesity, patients who had forceps delivery, shoulder dystocia, and macrosomia had the highest incidence of fourth-degree laceration (294.1 per 1000 vaginal deliveries). The incidence of fourth-degree perineal laceration decreased by 11.9% over time (P trend=.004); moreover, forceps delivery, vacuum-assisted delivery, and episiotomy decreased by 3.8%, 7.6%, and 29.5%, respectively (all, P trend<.05). CONCLUSION: This national-level analysis suggests that patients with obesity are less likely to have obstetric anal sphincter injuries at the time of vaginal delivery. Furthermore, this analysis confirms other known risk factors for fourth-degree laceration, such as forceps delivery, vacuum-assisted delivery, episiotomy, and shoulder dystocia. However, we noted a decreasing trend in fourth-degree lacerations, which may be due to evolving obstetrical practices.